2012
DOI: 10.1371/journal.pone.0035102
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Composition of the Human Eye: Are Red Blood Cells a Good Mirror of Retinal and Optic Nerve Fatty Acids?

Abstract: BackgroundThe assessment of blood lipids is very frequent in clinical research as it is assumed to reflect the lipid composition of peripheral tissues. Even well accepted such relationships have never been clearly established. This is particularly true in ophthalmology where the use of blood lipids has become very common following recent data linking lipid intake to ocular health and disease. In the present study, we wanted to determine in humans whether a lipidomic approach based on red blood cells could reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 93 publications
(134 reference statements)
7
84
0
Order By: Relevance
“…In 2008, a research group from France reported a negative correlation of retinal DHA with orbital fat DHA ( 8 ), which is in agreement with our present results. A follow-up study by this same group examined RBCs and retinal lipids from nine elderly donors and found that GC with fl ame ionization detection yielded …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In 2008, a research group from France reported a negative correlation of retinal DHA with orbital fat DHA ( 8 ), which is in agreement with our present results. A follow-up study by this same group examined RBCs and retinal lipids from nine elderly donors and found that GC with fl ame ionization detection yielded …”
Section: Discussionsupporting
confidence: 93%
“…We used a high-sensitivity GC/MS analytical protocol developed in our laboratory ( 30 ) that requires minimal amounts of valuable retinal tissue; typically, a single 4-6 mm punch is suffi cient. Our GC/MS method readily allows for the distinction between n-3 and n-6 LC-PUFAs and VLC-PUFAs, which is in contrast to LC/MS methods ( 8, 39 ), which do not permit distinction between these two important classes of lipids, one of which is generally anti-infl ammatory and associated epidemiologically with decreased AMD risk and cumbersome tools, and nutritional researchers have therefore developed and validated biomarkers of shortterm (weeks), medium-term (months), and long-term (years) dietary intake, but until now, there has been relatively little linkage between these biomarkers and retinal tissue levels in adult humans ( 7,8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent study indicated that cisplatin led to neurotoxic effects in human and animals via induction of lipid peroxidation [59]. Our present work showed that cisplatin produced a significant increase in MDA level that induced lipid peroxidation in the brain tissues accompanied with suppression in SOD activity [60].…”
Section: The Biochemical Effectssupporting
confidence: 59%
“…The developing retina in premature infants is particularly susceptible to oxidative damage because of its high proportion of long chain polyunsaturated fatty acid (PUFA) [130,131]. High-energy short-wavelength visible light, high oxygen fluctuation and high metabolic activity in the immature retina also promote the production of ROS which are highly reactive and readily react with lipid, protein and nuclear acids in the retina, thereby resulting in irreversible damage to various cell structures.…”
Section: Macular Xanthophyll Lutein/zeaxanthin and Retinopathy Of Prementioning
confidence: 99%